Decrease in Labour Pain at First Stage with Birthing Ball Techniques in Primigravida Mothers - Anandita, Mella Yuria Rachma; Gustina, Irwanti (Program Studi S1 Kebidanan - Fakultas Ilmu Kesehatan Universitas PGRI Adi Buana Surabaya, 2024)
Labour pain causes the release of stress hormones, resulting in decreased uterine contractions and uteroplacental circulation, reduced blood flow and oxygen to the uterus, which makes pain impulses multiply. One technique to reduce labour pain non-pharmacologically is with a birthing ball. This study aims to determine the effectiveness of birthing balls in reducing first-stage labor pain in primigravida. This study used a quick experiment with a Nonequivalent Control Group Design. The population was all mothers giving birth in three Depok City maternity centers. The sample used a purposive sampling technique, with as many as 50 samples of experimental and control groups. Data analysis using two dependent means or dependent T-test (paired T-test). Before the birthing ball intervention, the experimental group felt moderate labour pain by 76%, after the birthing ball technique experienced a decrease in the moderate pain scale by 64%. Analysis results show an average decrease in pain levels of labouring mothers who use the Birthing Ball 0.38. The results of statistical calculations also mention a p-value of 0.0001, meaning that the use of the Birthing Ball has proven effective in reducing first-stage labour pain. Birthing Ball in labour increases endorphin release, effectively reducing labour pain.